2008
DOI: 10.3233/ch-2008-1114
|View full text |Cite
|
Sign up to set email alerts
|

Time dependent variation of human blood conductivity as a method for an estimation of RBC aggregation

Abstract: Time variation of whole human blood conductivity and shear stresses were investigated at rectangular and trapeziumshaped Couette viscometric flow under electric field of 2 kHz. The kinetics of conductivity signals were recorded both under transient flow and after the complete stoppage of shearing at shear rates from 0.94 to 94.5 s −1 and temperatures T = 25 • C and 37 • C. Contraves Low Shear 30 rotational viscometer as a base unit and a concurrent measuring system, including a device, developed by the conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 1 publication
(2 reference statements)
0
20
0
Order By: Relevance
“…By applying shear stress to the blood sample with external driving systems (i.e., an SP [34], pinch valve [16], or stirring motor [35]), the RBCs in the blood sample are aggregated or disaggregated, depending on the shear rate. Several quantification methods, such as light intensity (i.e., transmission, and back-scattering) [16], electrical conductivity [36,37], microscopic RBC images [38][39][40], ultrasonic images [41], and optical tweezers [42] have been suggested for obtaining temporal variations of RBCs aggregation. As another approach, RBC aggregation can be quantified by measuring the sedimentation distances of RBCs in a blood sample during a specific duration (i.e., ESR).…”
Section: Introductionmentioning
confidence: 99%
“…By applying shear stress to the blood sample with external driving systems (i.e., an SP [34], pinch valve [16], or stirring motor [35]), the RBCs in the blood sample are aggregated or disaggregated, depending on the shear rate. Several quantification methods, such as light intensity (i.e., transmission, and back-scattering) [16], electrical conductivity [36,37], microscopic RBC images [38][39][40], ultrasonic images [41], and optical tweezers [42] have been suggested for obtaining temporal variations of RBCs aggregation. As another approach, RBC aggregation can be quantified by measuring the sedimentation distances of RBCs in a blood sample during a specific duration (i.e., ESR).…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation denotes the formation of reversible clumps of RBC under sufficiently low shear stresses (21,22). It has been reported that electrical properties of red cell suspensions also change during aggregation (11,13,14,(23)(24)(25)(26)(27). The electrical properties of blood plasma and blood cells differ from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive studies were performed during the last few decades for characterizing the RBC aggregation and using it as a parameter for diagnostics and monitoring of the pathological states. Different methods, such as laser beam scattering on blood suspension, 5,6 microscopic image analyses, 7 measurement of electrical conductivity, 8 electrophoresis, 9 and others, 10 were developed to quantify the RBC aggregation. On the other hand, for assessing RBCs interaction mechanism, methods such as micropipette aspiration technique, 11 scanning electron microscopy, 12 atomic force microscopy, 13 and optical tweezers 14 were implemented.…”
Section: Methods For Studying Rbc Aggregationmentioning
confidence: 99%